2021
DOI: 10.1002/onco.13883
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Management of Adverse Reactions in Patients with Advanced Endometrial Carcinoma Treated with Lenvatinib Plus Pembrolizumab

Abstract: Background. The combination of lenvatinib plus pembrolizumab has shown efficacy in treatment of advanced endometrial carcinoma that is not MSI-H or dMMR following prior systemic therapy in any setting in the open-label, single-arm, phase 1b/2 Study 111/KEYNOTE-146. With the exception of hypothyroidism, the safety profile of the combination was comparable to that of each monotherapy. Given the medical complexity and fragility of endometrial carcinoma patients, further characterization of adverse reactions (ARs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Indeed, despite dose reductions, median tumor size decreased over time ( 18 ). The median time to the first onset of most frequent adverse events occurred approximately 3 months after treatment initiation in both all-comer and pMMR populations: adverse events with the shortest median time to onset included hypertension and musculoskeletal disorders, while hypothyroidism, palmar-plantar erythrodysesthesia (PPES), and weight decrease, which can be considered as a cumulative effect of vomiting, nausea, and musculoskeletal disorders, had a long time to onset ( Figure 1 ) ( 19 ). Therefore, some adverse events should be monitored and prevented from the beginning of the treatment.…”
Section: Safety Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, despite dose reductions, median tumor size decreased over time ( 18 ). The median time to the first onset of most frequent adverse events occurred approximately 3 months after treatment initiation in both all-comer and pMMR populations: adverse events with the shortest median time to onset included hypertension and musculoskeletal disorders, while hypothyroidism, palmar-plantar erythrodysesthesia (PPES), and weight decrease, which can be considered as a cumulative effect of vomiting, nausea, and musculoskeletal disorders, had a long time to onset ( Figure 1 ) ( 19 ). Therefore, some adverse events should be monitored and prevented from the beginning of the treatment.…”
Section: Safety Datamentioning
confidence: 99%
“…Furthermore, being proactive in the management of gastrointestinal adverse events may avoid weight loss. Patients’ and clinicians’ education and preventive strategies need to be implemented ( 18 , 19 ).…”
Section: Safety Datamentioning
confidence: 99%
See 2 more Smart Citations
“…A post hoc analysis found that selected AEs, such hypertension, fatigue, nausea/vomiting, diarrhea, decreased appetite/weight loss, hypothyroidism, palmar–plantar erythrodysesthesia, musculoskeletal pain, stomatitis and proteinuria, developed within the first 10 weeks of treatment. G ≥ 3 fatigue, hypertension and nausea occurred in ≥5% of patients [ 102 ]. AEs may be managed with concomitant supportive medications and lenvatinib dose modifications.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%